Advanced one-dimensional heterogeneous model for high temperature water gas shift membrane reactors - El Bazi, Wail; El-Abidi, Abderrahim; Yadir, Said; Messnaoui, Brahim (Center of Biomass & Renewable Energy (CBIORE), 2025)
To predict the behavior of small-scale WGS membrane reactors, a new model based on the 1D heterogeneous approach was developed. Unlike most studies, which rely on 1D pseudo-homogeneous models—typically limited to reactors filled with small catalyst particles which are prone to misestimating catalytic effectiveness when larger catalyst grains are used in which mass transfer resistance is usually considered only within the dense membrane layer which a valid assumption only when this layer is thick, the proposed model adapts to a wide range of catalyst sizes and geometries and also accounts for resistance in the porous stainless steel support of the membrane. This makes it suitable when the dense layer is thin.Comparison with experimental data under various conditions validated the model’s ability to predict the behavior of reactors packed with large catalyst particles (Vgrain ≈ 169 mm³). Therefore, the developed 1D heterogeneous model accurately predicts membrane reactor behavior without resorting to more complex 2D models. Simulations highlighted the significant influence of particle geometry on the catalyst effectiveness factor throughout the reactor, while its impact on carbon monoxide conversion, hydrogen partial pressure, and the temperature profile is especially pronounced near the reactor inlet. Additionally, results showed that sweep gas use accelerates the reaction and aids hydrogen permeation. Finally, CO conversion in the membrane reactor reached 1.3 times that of a conventional fixed-bed reactor.